Aspectos da ecologia de Lutzomyia longipalpis (Diptera: Psychodidade) em áreas de transmissão de leishmaniose visceral no município de Paulo Afonso - BA - Pereira, Luciano de Araújo (2011)
In the Americas, Lutzomyia longipalpis has been incriminated as a vector of visceral leishmaniasis in virtually all areas in which this disease. The survey was conducted around the homes and in households of three urban households. The catches were made weekly with automatic light traps of CDC in the period December 2009 to November 2010 at City Center in the neighbor Centennial and the Village Moxotó. We captured 586 specimens belonging to three species: Lutzomyia longipalpis, Lutzomyia goiana and Lutzomyia sallesi. Specimens of the latter two-species turnover were males and two were rare, while Lutzomyia longipalpis was considered abundant and was present in all seasons of capture. Surprising to the number of specimens captured was higher in downtown compared to other neighborhoods. The center has had 79% of specimens caught, the neighbor Centennial for 15% and the Village Moxotó, most peripheral of all this catchtions, had only 6% of all insects captured. The frequency of males (57%) was higher than females (43%) and this difference in the amount of males and females was also observed in the three seasons of capture. As for the behavior endofile and exophilic: 92 specimens were caught indoors (16%) and 494 in the peridomicile (84%). At all locations catch the percentage was higher in specimens caught outside the home. The climatic data of temperature and relative humidity were obtained using a digital hygrometer and rainfall values referring to this period were obtained from the Meteorological Station of Paulo Afonso - Bahia. Although already established in the literature for the vector, temperature, relative humidity and rainfall were statistically not significant relationship between these factors justify the frequency of sandflies in Paulo Afonso Bahia.